2017
DOI: 10.4103/2152-7806.199560
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intubation success and glottic visualization using King Vision and C-MAC videolaryngoscopes in patients with cervical spine injuries with cervical immobilization: A randomized clinical trial

Abstract: Background:Glottic visualization can be difficult with cervical immobilization in patients with cervical spine injury. Indirect laryngoscopes may provide better glottic visualization in these groups of patients. Hence, we compared King Vision videolaryngoscope, C-MAC videolaryngoscope for endotracheal intubation in patients with proven/suspected cervical spine injury.Methods:After standard induction of anesthesia, 135 patients were randomized into three groups: group C (conventional C-MAC videolaryngoscope), g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…compared conventional C-MAC, CMAC-D and Kings Vision video laryngoscopes and found comparable IDS scores in C-MAC group and Kings Vision group ( P = 0.340). [13] However, the median score of IDS was “0” in all the three groups. In the present study, mean difference in ADS, C-L grade and IDS between the two groups was statistically not significant, and both the devices are equally efficacious for ease of intubation.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…compared conventional C-MAC, CMAC-D and Kings Vision video laryngoscopes and found comparable IDS scores in C-MAC group and Kings Vision group ( P = 0.340). [13] However, the median score of IDS was “0” in all the three groups. In the present study, mean difference in ADS, C-L grade and IDS between the two groups was statistically not significant, and both the devices are equally efficacious for ease of intubation.…”
Section: Discussionmentioning
confidence: 97%
“…[611] A study compared GlideScope with CMAC in patients with cervical spine immobilisation and reported both devices to be effective, although intubation was more often successful with GlideScope. [12] Although video laryngoscopes have been compared with other airway devices in manikin studies[10] or in simulated difficult airway scenario,[16111213] studies are scant in patients with real cervical spine injury/pathology. [12] Bruck et al ., reported that both CMAC and GlideScope provided an excellent glottic view in patients with cervical spine immobilisation, but tracheal intubation was more often successful with Glide Scope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These victims require constant stabilization of their cervical spine. As shown in many studies, the use of an orthopedic collar limits the opening of the patient's oral cavity [17,18], as well as limits head movement which results in markedly lower rates of first-time intubation success with the use of direct laryngoscopes [19,20]. In a study by Kłosiewicz et al, the use of a standard Macintosh laryngoscope was compared to the use of the TotalTrack VLM device (Fig.…”
Section: Endotracheal Intubation Techniques In Literaturementioning
confidence: 99%
“…For the purposes of the study, the anterior portion of the collar was removed, and the patient's chin was stabilized by hand. The first attempt intubation success rate was 93.3% vs 100% respectively, while the total procedure time was comparable at 24.9 ± 7.2 seconds [17]. Meanwhile, Smereka et al compared the C-MAC video laryngoscope with the Macintosh laryngoscope.…”
Section: Endotracheal Intubation Techniques In Literaturementioning
confidence: 99%